PENGARUH LABEL HALAL, HARGA, DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK LIPSTIK PADA MAHASISWI PROGRAM STUDI EKONOMI SYARIAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS - Emelia; Sri Deti; Oskar Hutagaluh (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Appearance is a psychological portrait, like a tool to communicate with others. The large number of people who want and need beauty care products will greatly help shape the market potential for beauty care products, so that many companies are taking advantage of this opportunity to produce cosmetics according to their needs. The needs and desires of consumers for cosmetics can lead to increasingly fierce competition in the cosmetic industry market. This study aims to determine the effect of Halal Labels, Prices and Advertising on Lipstick Product Purchasing Decisions in Islamic Economics Study Program Students, Faculty of Islamic Economics and Business, Islamic Institute of Religion, Sultan Muhammad Syafiuddin Sambas. The subjects of this study were female students of the Islamic Economics Study Program, Faculty of Islamic Economics and Business with a total sample of 74 female students. The object of this study is Halal Labels, Prices and Advertising on the Purchase Decision of Lipstick Products. The method used is quantitative with the type of research that is field research. This study uses multiple linear regression analysis method. The sample selection technique used is purposive sampling. The analytical method used in this study includes validity test, reliability test, classic assumption test and hypothesis testing through multiple linear regression analysis test. The results show that Halal label has a positive effect on purchasing decisions, this can be seen from the significance of 0.001 < 0.05 and can be seen from the tcount of 3.616, which means tcount 3.616 > ttable 1.66691; price has a no effect on purchasing decisions, this can be seen from the significance of 0.045 < 0.05 and can be seen from tcount of 1,045 which means tcount of 1,045 > ttable of 1,66691; and advertising has a positive effect on purchasing decisions, this can be seen from the significance of advertising of 0.017 < 0.05 and can be seen from tcount of 2.456 which means tcount 2.456 > ttable 1.66691.